Primary commodities : market developments and outlook - International Monetary Fund; The Commodities Division of the Research Department (Washington, D.C. : The Division, 1986)
The study provides an analysis of the market developments in 1988 with respect to primary commodities and the outlook for these commodities.
aia 12/02/2019
Loans
Keywords: Commodity exchanges; Primary commodities; Produce trade; Commercial products; Bourses de marchandises; Produits de base; Produits agricoles; Internationale economie; Internationale financiën.; Commercial products; Commodity exchanges; Primary commodities; Produce trade